Features of the use of PID controllers when controlling evaporators - Зубков, О. В.; Свид, І. В.; Мальцев, О. С. (MC&FPGA, 2020)
In the work, the features of the use of PID regulators for controlling evaporators are theoretically and experimentally analyzed, an algorithm for controlling the heating element of the evaporator is developed, and practical recommendations are given for choosing the parameters of the PID controller.
Keywords: PID controller; evaporator; microcontroller; algorithm; vapor